2020
DOI: 10.1063/1.5131490
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of diamagnetic drift on neoclassical double tearing modes based on four-field reduced MHD model

Abstract: The explosive behavior of neo-classical double tearing mode (NDTM) is numerically investigated by a reduced four-field-drift-magnetohydrodynamic code [Ye et al., Nuclear Fusion 59, 096044 (2019)] with the bootstrap current effect. It is numerically observed that the explosive burst of NDTM can be absolutely suppressed by diamagnetic drift flow. The dependence of the critical value of diamagnetic drift flow V0*c for avoiding the explosion on typical plasma parameters is numerically studied in detail. It is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For instance, the simulation results are adopted to explain experimental observations in ASDEX-U [34] and DIII-D. [56] In simulations related to two-fluid dynamics, cylindrical geometry has also been extensively employed. [42,44,45,57] Simulation results have demonstrated the ability to elucidate certain phenomena observed in experiments. Paz-Soldan et al found alignment between simulation results by TM1 code, a nonlinear two-fluid MHD model with cylindrical geometry, and experimental island healing.…”
Section: Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the simulation results are adopted to explain experimental observations in ASDEX-U [34] and DIII-D. [56] In simulations related to two-fluid dynamics, cylindrical geometry has also been extensively employed. [42,44,45,57] Simulation results have demonstrated the ability to elucidate certain phenomena observed in experiments. Paz-Soldan et al found alignment between simulation results by TM1 code, a nonlinear two-fluid MHD model with cylindrical geometry, and experimental island healing.…”
Section: Model Equationsmentioning
confidence: 99%
“…[39,40] Hence, there has been an increasing focus on research related to two-fluid effects in recent years. For example, studies have been carried out on the control of NTMs by resonant magnetic perturbations, [41][42][43] on the suppression of the onset of neoclassical double tearing modes by diamagnetic drift, [44] on the systematic numerical simulation of the mode penetration in NTMs, [45] on the influence of Hall effect on TMs [46,47] and on the influence of diamagnetic drift on MHD stability in DIII-D experiments. [48] Despite great progress having been made in two-fluid studies, further research is still required to simulate multi-helicity NTMs based on two-fluid theory.…”
Section: Introductionmentioning
confidence: 99%